Sitti Raihanun Zainuddin Abdul Madjid, Female Scholar of the 21st Century: Pioneer in Gender Transformation and Islamic Education in Lombok-West Nusa Tenggara - Lalu Gede Muhammad Zainuddin Astani; Ulyan Nasri; Fahrurrozi; Muhammad Thohri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study investigates the pivotal role of Sitti Raihanun Zainuddin Abdul Majid as a 21st century female Islamic scholar who pioneered gender transformation and Islamic education in Lombok, West Nusa Tenggara. The research aims to uncover her influence in reshaping gender roles through her leadership in Nahdlatul Wathan (NW) and her extensive contributions to building educational institutions. Anchored in feminist theories, social transformation frameworks, and female leadership paradigms, this study contextualizes her role in the broader discourse on gender equality in Islamic education. Employing a qualitative descriptive method with a hermeneutic approach, data were collected through in-depth interviews with NW members, local community figures, and Sitti Raihanun herself, as well as analysis of organizational documents and her public speeches. The findings reveal that her leadership was shaped by a strong moral and religious upbringing, institutional charisma, and a strategic vision to promote women’s leadership within Islamic contexts. Despite facing patriarchal resistance and leadership controversies, she effectively implemented a transformative and charismatic leadership model. Her efforts resulted in the establishment of hundreds of Islamic schools and an expanded da'wah network across Indonesia. This study contributes to a nuanced understanding of gender transformation in Islamic education and highlights the importance of inclusive female leadership in advancing educational and societal change.